Childhood shocks and fertilit: Evidence from parental job loss - Krista Riukula (The Research Institute of the Finnish Economy (ETLA), 2024)
Do economic shocks experienced in childhood carry on to the fertility outcomes in adulthood and if they do, how? Using plant closures from the years 1991-1993 in Finland, I find that maternal and paternal job loss have asymmetric effects on children's fertility outcomes. Maternal job loss increases the probability of a son becoming a parent, while paternal job loss decreases it. For paternal job loss, I find negative effects on son's other outcomes, such as having a spouse, earnings, and employment which might drive the effects on their fertility outcomes. Instead, maternal job loss has no effect on son's other outcomes. Hence, fertility might be affected through other channels such as changes in parent-child relationship quality. For daughters, I find effects on timing; they have children earlier due to maternal job loss and later due to paternal job loss. There are no effects on daughters' other outcomes suggesting that the effects on fertility outcomes might work through other channels. The results might be best interpreted in terms of spousal roles; mothers might shift more energy towards their role as a caregiver, while paternal job loss can be more stressful if the father fails to fulfill his role as a breadwinner.
Keywords: J13; J63; 330; Job loss; Fertility; Childhood shocks